Ampliação do tempo escolar: o trabalho docente nas escolas públicas de tempo integral da rede municipal de educação de Goiânia - Vicente, Milene do Amaral Ferreira (2017)
In 2015, the Municipal Department of Education changed the organization of the Municipal Full-time Schools from Goiânia, restructuring both form and content of the teaching work. Teachers start to do their full time work, in only one institution and with specific conditions. In this context, this research sought to understand the different meanings of the teaching work in this concrete reality. The chosen path for this apprehension was through data collection in field research; bibliographical review on the historicity of education and the full-time schools in Brazil and in the public education of Goiânia; appropriation of the contemporary movements of reorganization of the teaching work with a view to the productive restructuring of the capital and documentary analysis of the Municipal Office of Goiânia referring to the orientations and legal determinations in the pedagogical and organizational scope. The data analysis was developed by systematizing the data through Centers of Significance (AGUIAR, 2009; AGUIAR and OZZELA, 2006; 2013), which allowed us to understand that full-time teaching in an institution with full-time attendance reveals that the change of the activity of the teachers in their content and form implies in the formulation of discourses that point to integral and procedural relations of teaching and learning. Contradictory, the current condition of teaching work, on one hand, was described as propitious for the accomplishment of humanizing activities of teachers; on the other hand, revealed the imbalance between working time and nonworking time, typical of capitalist sociability, that hinder omnilateral ways of being and living.